PENGARUH HYPNOBIRTHING TERHADAP TINGKAT NYERI PADA KALA I FASE AKTIF PRIMIPARA DI KLATEN - Kanthi Surati (Poltekkes Kemenkes Jakarta III, 2016)
Pain in childbirth is painful uterine contractions that can lead to increasedactivity of the sympathetic nervous system. Various nursing actions can be done toalleviate the pain felt maternal among others with hypnobirthing method. As aresult of this pain causes many mothers who choose to labor with sectio Caesariain Klaten, Central Java amounted to 24.05% in 2012. The research objective wasto determine the effect of hypnobirthing on the level of pain in the active phase ofthe first stage primiparas in Klaten. This type of research is quantitative. Thepopulation is all normal vaginal delivery when the first active phase 30 peoplewere being treated in Klaten. The sampling technique used is total sampling. Theanalysis showed no significant difference on the level of pain in patients who dohypnobirthing with patients without hypnobirthing in Klaten in 2013 with p value0.000. With hypnobirthing pregnant women are taught to calm the mind byfocusing and followed by self-hypnosis with affirmations and suggestions toachieve the birth of a healthy, comfortable and smooth. Conclusion: there is asignificant difference on the level of pain in patients who do hypnobirthing withpatients without hypnobirthing.